Contingent maternities? Maternal claims‐making in third party reproduction. Issue 8 (8th June 2017) - Johnson, Katherine M.
Abstract: The new reproductive technologies have significantly impacted definitions of motherhood. Historically, mothers were defined through the act of giving birth, but egg donation, embryo donation, and surrogacy disrupt this. Now multiple women can potentially claim maternity through gestational, genetic, legal, and social ties. Although there is some legal precedent for designating parentage, there is no simple solution to identify the 'true' mother. I address maternal claims‐making in third party reproduction via a content analysis of US patient literature for infertile women. Major tensions arise over which link to privilege, especially regarding genetic versus gestational ties in egg donation versus surrogacy; however, adding embryo donation to the analysis illuminates another crucial dimension previously overlooked – that heterosexual women's maternal claims are supported by their partner's paternity claims. Ultimately, I argue that although reproductive organisational discourse carefully constructs credible options for maternal claims‐making, contemporary reproductive medicine does not define maternity through assisted reproduction as a truly autonomous connection. Rather, maternity is highly contingent and thus potentially discreditable.